(untitled) (Fiep Bulletin - online, 2011)
In the search for a comfortable and productive workplace, professionals of people management must look tools so that the employees feel motivated and trained. The values of the employees must be lined up with the ones of the organization, so that both can commune of similar ideas. For this, there are many ways of training that can help. An interesting way to align values are the experiential trainings, so that participants can experience their actions in full, and can internalize much more the process than a traditional lecture. Within this form of training, there are the adventure races, which are multi sports activities in the nature, and also aim to work on values that can be applied in the workplace. SESI SC (Industrial Social Service of Santa Catarina), held every year adventure races, with the audience of the industrial workers from the companies of the state. In September 2009, SESI promoted another adventure race, and in the end of the race, were conducted interviews with the participants. The goal was to know the profile of the participants, and also what values they have identified in adventure racing. In addition, was asked the participants, what values they applied in their workplace and also in your life, to make a relation with values identified in adventure racing. The results showed that this activity can be a useful tool in the activation process of value, because many values identified in the test are also applied in the corporate environment and in people’s lives.